Clinical characteristics in subcortical ischemic white matter disease Características clínicas na doença isquêmica da substância branca subcortical - Gilberto Sousa Alves; Carlos Eduardo de Oliveira Alves; Maria Elisa de Oliveira Lanna; Letice Ericeira-Valente; Felipe Kenji Sudo; Denise Moreira; Eliasz Engelhardt; Jerson Laks (Arquivos de Neuro-Psiquiatria, 2009)
BACKGROUND: Vascular white matter lesions (WML) represent one of the main neuroimage findings in individuals older than 65 years and its clinical significance is still partially understood. OBJECTIVE: To describe and analyze the clinical profile of a high severity sample with WML focusing on the frontal executive control. METHOD: Outpatients (n=20) with high severity WML evaluated with magnetic resonance imaging were selected using the Fazekas scale. RESULTS: Most patients (n=17; 85%) presented an altered Trail Making Test ratio (section B/section A); on verbal fluency, 15 individuals (75%) performed below the cutoff score. Apathy (5.9 ± 4.65) and depression (3.05±3.67) were frequent as assessed by the Neuropsychiatric Inventory. The impairment in functional activities strongly correlated with apathy (r=0.814, p<0.001) and verbal fluency (r=0.744, p<0.001). CONCLUSION: Executive dysfunction, apathy, and ratio depression were the main characteristics found. Extension of WML may have distinct impact on the clinical picture, but further studies with methodological adjustments are necessary to provide more definitive conclusions. FUNDAMENTO: Lesões vasculares em substância branca (LSB) são um dos principais achados de neuroimagem em indivíduos acima de 65 anos e sua importância em termos clínicos é ainda parcialmente conhecida. OBJETIVO: Descrever e analisar o perfil clínico de amostra com LSB grave enfocando as alterações do controle executivo frontal. MÉTODO: Pacientes ambulatoriais (n=20) avaliados pela ressonância nuclear magnética e com maior proporção de LSB foram selecionados através da escala de Fazekas. RESULTADOS: A maioria dos pacientes (n=17; 85%) apresentou alteração na proporção teste das trilhas (seção B/A); na fluência verbal, 15 indivíduos (75%) apresentaram desempenho abaixo do ponto de corte. Apatia (5,9±4,65) e depressão (3,05±3,67) foram freqüentes na avaliação pelo Inventário Neuropsiquiátrico. O prejuízo nas atividades funcionais correlacionou-se fortemente à apatia (r=0, 814, p<0,001) e à fluência verbal (r=0, 744, p< 0,001). CONCLUSÃO: Disfunção executiva, apatia e depressão foram as principais características encontradas. A extensão e localização das LSB parecem exercer um impacto distinto nas manifestações clínicas, porém estudos futuros com ajustes metodológicos são necessários para conclusões mais definitivas.